Parenting Stress as a Correlate of Cognitive Behavior Therapy Responsiveness in Children With Autism Spectrum Disorders and Anxiety. (September 2015) - Weiss, Jonathan A.; Viecili, Michelle A.; Bohr, Yvonne
Children with autism spectrum disorder (ASD) often show high rates of anxiety, and cognitive behavior therapy (CBT) is recognized as an emerging evidence-based practice. Eighteen children (8–12 years of age, M = 9.5, SD = 1.34; male: n = 15) with ASD and significant anxiety problems participated in a 12-session group "Coping Cat" intervention together with their parents. Statistically significant reductions were noted across measures of parent-reported child anxiety, with 50% of children demonstrating clinically meaningful improvements using the conservative Reliable Change Index. Significant correlations were found between change in parenting stress and change in child anxiety from pre- to post-treatment. These results are applicable to the community service sector, where the Coping Cat program is commonly utilized. Due to the high prevalence of anxiety disorders in children with ASD, further research is needed to advance capacity building to help meet the significant needs of youth with ASD and anxiety.